KAJIAN PENGUASAAN DAN PEMANFAATAN LAUT DANGKAL KOTA SIBOLGA - Nababan, Melissa; Siregar, Hari; Nainggolan, Justinos (Jurnal Sains dan Teknologi ISTP, 2025)
The human population, particularly in the coastal areas of Sibolga, continues to increase, making it necessary to find solutions for the city's development. Land reclamation offers benefits and can support the city in providing land for various needs, such as urban expansion, coastal area management, marine tourism development, and more. From an economic perspective, the development of commercial areas will undoubtedly generate significant revenue. The assumption used here is that the more commercial areas are developed, the more they will contribute to increasing the region’s locally generated revenue (PAD). However, it must also be noted that reclamation is a form of human intervention in the natural balance of the coastal environment, which is always in a state of dynamic equilibrium. This intervention can lead to ecological changes such as alterations in current patterns, coastal erosion, and sedimentation, potentially disrupting environmental stability.The objective of this Coastal Reclamation Analysis for Sibolga City is to provide recommendations on the feasibility of coastal reclamation as an effort to obtain additional land for the expansion of Sibolga City and to support future urban planning and development.